Kemampuan Pedagogical Content Knowledge (PCK) Guru Biologi SMA Kelas X di Kabupaten Sragen dalam Menyusun Modul Ajar Tahun Ajaran 2022/2023 - Anggun Ella Indriyani; Hariyatmi Hariyatmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
In the world of education, the curriculum is very influential on the learning process. With the change in curriculum, the success of the teaching system is also greatly supported by the presence of educators, namely teachers who are professional during the teaching and learning process. Optimal learning can be obtained if a teacher has some knowledge. a teacher has competence, namely pedagogic, professional, social and personality competencies. The teacher's ability to plan and prepare for the learning process is found in pedagogic abilities.The goal of this study is to find out the ability of Pedagogical Content Knowledge (PCK) high school biology teachers in Sragen Regency in preparing lesson plans. The current study is a qualitative descriptive investigation using a purposive sampling approach. The samples used were 5 Biology high school teachers including 3 public high schools and 2 Muhammadiyah high schools. The findings indicated that the CK ability of biology teachers in Sragen regency high school in preparing the teaching modules for the 2022/2023 academic year was good (87.358%), the ability of the biology teacher's PK was good (78.5924%), and the biology teacher's PCK ability was sufficient (68.752%).